Environmental Inequality and Economic Valuation - Jasper N. Meya (Environmental and Resource Economics, 2020)
I study how the economic value of a heterogeneously distributed environmental public good depends on how the endowment with this good and income are distributed. I find that the effect of environmental inequality on the societal willingness to pay (WTP) for the environmental good is determined both by its substitutability and by the correlation of its provision with income. Specifically, environmental inequality decreases societal WTP for substitutes, but this effect is reversed if the environmental good is a complement or distributed strongly in favour of richer households. Moreover, I show that richer households living in places where environmental good endowment is high increases (decreases) societal WTP if and only if the environmental good is a substitute for (complement to) consumption goods. I propose novel adjustment factors for structural benefit transfer to control for differences in the spatial distribution of environmental goods. Using forest preservation in Poland as an empirical example, I find that societal WTP is up to 4% higher for equal access to forests and up to 8% higher for an equal distribution of both income and access to forests.
Keywords: D63; Q51; 330; Inequality; WTP; Heterogeneously distributed public good; Spatial distribution; Benefit transfer; Forest ecosystem services